Conservation Status of the Amphibians of Brunei Darussalam - Das, Indraneil; Grafe, T. Ulmar (Natural History Publications (Borneo) Sdn. Bhd, 2014)
Brunei Darussalam is located on the northern coast of the island of Borneo and has a total land area of 5766 km2 . It is divided into two disjunct regions: the districts of Brunei/Muara, Tutong, and Belait in the west and Temburong in the east (Fig. 1). The two parts are completely surrounded and separated by the Malaysian state of Sarawak. The major forest types in Brunei are (1) lowland mixed-dipterocarp rainforests, (2) peatswamp forests, (3) heath forests (Kerangas), and (4) mangrove forests (Ashton et al. 2003).